Leadership in Action : Face to Face - Bridging the Divide - A Conversation with Tsun-Yan Hsieh - Rush, Editor Stephen (Center for Creative Leadership, 2006)
Tsun-Yan Hsieh recently spoke with Leadership in Action contributing editor Joyce Jenkins about leadership issues in Asia.